Evaluation of two fibrous clay minerals (sepiolite and palygorskite) for CO2 Capture. Issue 4 (August 2018) - Cecilia, J.A.; Vilarrasa-García, E.; Cavalcante, C.L.; Azevedo, D.C.S.; Franco, F.; Rodríguez-Castellón, E.
Graphical abstract: Highlights: Sepiolite and palygorskite have been evaluated for their potential for CO2 capture. Sepiolite and palygorskite were modified by microwave-assisted acid treatment and impregnated with amines. Raw sepiolite hashigh potential in CO2 capture at 25 °C than palygorskite due to the lower microporosity of the later. The double functionalization of sepiolite with APTES-PEI led to the highest CO2 adsorption capacity. Abstract: Two fibrous clay minerals (sepiolite and palygorskite) have been employed as adsorbents to assess their adsorption capacity of pure CO2 in a volumetric setup. The raw sepiolite reached a CO2 uptake of 1.48 mmol g −1 due to the presence of nanocavities acting as a molecular sieve. Both sepiolite and palygorskite were modified by microwave-assisted acid treatment, which led to an increase in specific surface area and pore volume due to Mg 2+ leaching, particularly in the case of sepiolite. However, the partial digestion of these fibrous structures does not improve CO2 adsorption uptake due to the progressive increase of the size of nanocavities. In a next step, both fibrous clay minerals were functionalized with amine species by different procedures (grafting with (3-Aminopropyl) triethoxysilane (APTES), impregnation with polyethyleneimine (PEI) and double functionalization by grafting with APTES and then impregnation with PEI. In all cases, it can be observed that the incorporation of amine species favors the chemical interaction between the amines species and the CO2 molecules, although it also produces obstruction of the nanochannels so the adsorption takes place mainly on the outer surface of the fibers. Finally, the incorporation of amine species by double functionalization led to the highest CO2 adsorbed concentration of 2.07 mmol g −1 at 760 mm Hg and 65 °C due to a larger proportion of available amines sites as well as the use of higher adsorption temperature, which favored the diffusion of CO2 molecules within the adsorbent.